Enchancing the Compound Synergy by Developing the Servicescape and In-Store Promotion - Arya, Misha; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
The purpose of this final study is to enhance the synergy of The Compound. Designed with the concept of shared and integrated retail stores, this environment should create a positive overall synergy. however, the fact that there is an atmospheric imbalance and  inter-store relationship issues which resulted in one store’s bankruptcy, indicates that there is an opportunity for improvement for the overall synergy. By means of restoring the balance of The Compound. The first step starts with servicescape approach by reviewing the servicescape of The Compound itself. The purpose is to identify the weaknesses in regard to balance. To acquire such information this study used Zeithaml and Bitner’s theory of servicescape. Servicescape flaws causing the informational and atmospheric imbalance between the fore and the aft are of The Compound, influence the inter-store relationship which are major factor concerning the synergy of The Compound. Furthermore, regarding the interrelationships of the stores which affects the overall synergy, a quantitative approach were used. Defining the levels of interrelationships and the overall synergy. An imbalance occured in the nature of The Compound’s visitors. Traffic imbalance between the fore and the aft. Another imbalance also ocurred in terms of gender ratio. To enhance the synergy, all imbalance must be restored. A way to restore this imbalance is by developing a better servicescape. And to further improve inter-relationship level, in-store promotional strategy is necessary. Only by then the overall synergy will increase. Keywords: Synergy, Servicescape, In-Store Promotion, Marketing, Retail Store.----------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.